# Hi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic

Hi, x^2 +(2+x)*5+46x=0 work-out the quadratic